2017
DOI: 10.1063/1.5002748
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced supercapacitance of activated vertical graphene nanosheets in hybrid electrolyte

Abstract: Supercapacitors are becoming the workhorse for emerging energy storage applications due to their higher power density and superior cycle life compared to conventional batteries. The performance of supercapacitors depends on the electrode material, type of electrolyte, and interaction between them. Owing to the beneficial interconnected porous structure with multiple conducting channels, vertical graphene nanosheets (VGN) have proved to be leading supercapacitor electrode materials. Herein, we demonstrate a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…These values of electrical resistance in F-VGNs are comparable to other graphene-based electrodes prepared by conventional chemical or thermal methods. These conclusions are consistent with the results of previous studies on vertical graphene and similar structures [27,28].…”
Section: Resultssupporting
confidence: 94%
“…These values of electrical resistance in F-VGNs are comparable to other graphene-based electrodes prepared by conventional chemical or thermal methods. These conclusions are consistent with the results of previous studies on vertical graphene and similar structures [27,28].…”
Section: Resultssupporting
confidence: 94%
“…[217] Oxygen plasma functionalization can make the surface near or completely hydrophilic, a higher amount of defects and hence higher ion diffusion rate at the electrode-electrolyte interface, excellent charge-transfer, reduced contact resistance and internal resistance ( Figure 15C,D). [10,163,211] It is also reported that the oxygen plasma activated biochar contains larger pore volumes with higher average pore size compared to that of chemically activated biochar. Not surprisingly, plasma-activated biochar exhibits around two times higher specific capacitance compared to that of chemically activated biochar although chemically activated biochar showed a higher BET surface area.…”
Section: Wettability and Porositymentioning
confidence: 99%
“…Most popular ways to simultaneously make the surface hydrophilic and introduce controlled O-functionalities in nanocarbon matrix are chemical activation or plasma treatment. [10,[212][213][214] It has been observed that KOH activation of the vertically graphenes assists in reducing its water contact angle by 30° along with pore formation, better graphitic quality and higher specific capacitance than that of the pristine material. [10] It is also possible to create mesoporous channels with micropores which significantly enhance the ion accessible surface area and ion diffusion onto the entire electrode surface.…”
Section: Wettability and Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…The actual temperature distribution of the furnace heated at 450, 465, 500, 550 and 600 °C is shown in Figure S2 Figures S3 and S4, Supporting Information). These 1D Mo 6 Te 6 wires are not vertical nanostructures such as vertical nanowall or vertical nanoflakes, [31,32] but horizontal 1D nanostructures. Figure 2d shows a Raman spectrum of the 1D Mo 6 Te 6 wires taken under 532 nm laser excitation, in which two characteristic peaks at 155.2 and 245.5 cm -1 are observed.…”
Section: Introductionmentioning
confidence: 99%